Penerapan Sistem Informasi Berbasis Web untuk Efisiensi BEM STMIK PESAT Nabire - Immanuel Candra Irawan; Yahya Arompau (Jurnal Teknologi dan Informatika, 2026)
This study aims to improve the performance of student organizations through the utilization of web technology in information system management. The case study focuses on the Student Executive Board (BEM) of STMIK PESAT Nabire, which faces challenges in data management, internal communication, and activity documentation. The research employed a software engineering approach using the Waterfall development model, which includes the stages of requirement analysis, system design, and implementation. The research instruments consist of technical documents such as use case diagrams and evaluative interviews to ensure the system's relevance to user needs. The system was developed using PHP and MySQL as the database. The implementation results indicate that the web-based information system facilitates BEM administrators in managing organizational activities more efficiently and in a structured manner. The findings imply that the appropriate application of web technology can enhance the operational effectiveness of student organizations and serve as a strategic solution for managing organizational information in higher education environments.